Routledge Handbook of Indian Cinemas. - Gokulsing, K. Moti (Taylor and Francis, 2013)
India is the largest film producing country in the world and its output has a global reach. After years of marginalisation by academics in the Western world, Indian cinemas have moved from the periphery to the centre of the world cinema in a comparatively short space of time. Bringing together contributions from leading scholars in the field, this Handbook looks at the complex reasons for this remarkable journey.Combining a historical and thematic approach, the Handbook discusses how Indian cinemas need to be understood in their historical unfolding as well as their complex relations.